Fuel concentration imaging inside an optically accessible diesel engine using 1-methylnaphthalene planar laser-induced fluorescence. (September 2014) - Trost, Johannes; Zigan, Lars; Leipertz, Alfred; Sahoo, Dipankar; Miles, Paul C
The performance and emissions of modern automotive diesel engines are highly dependent on the application of pilot injection technology. This technology also appears well suited for application to low-temperature combustion strategies. In this study, the first results of a new quantitative planar laser-induced fluorescence equivalence ratio measurement technique of pilot injections inside an optically accessible diesel engine are presented using 1-methylnaphthalene as a tracer in a mixture of the diesel primary reference fuels, n-hexadecane (cetane) and 2, 2, 4, 4, 6, 8, 8-heptamethylnonane (iso-cetane). This combination overcomes the shortcomings of mismatched fuel volatility and density associated with commonly used toluene/n-heptane/iso-octane planar laser-induced fluorescence techniques. A tracer characterization in a flow cell and a calibration in the internal combustion engine are performed. The internal combustion engine measurements illustrate the mixture formation process for a pilot injection. Even at low injection mass of 3 mg, a strong penetration of the pilot is observed; fuel hits the piston bowl wall and is redirected upward to the cylinder head. Small amounts of fuel are also found to have penetrated into the bottom of the piston bowl. At top dead center, the pilot injection is still not completely homogeneously distributed in the piston bowl, and local equivalence ratios of Φ > 1 are found in the bowl.